Підходи до реалізації апаратно-програмного навчального комплексу шрифту Брайля - Артамонов, Євген Борисович; Кременецький, Георгій Миколайович; Длужевський, Андрій Олександрович; Панфьоров, Олександр Володимирович (НТУ "ХПІ", 2015)
Розглядається реалізація апаратно-програмного навчального комплексу, який представляє собою тактильний дисплей для виведення шостикрапкового символу в системі Брайля на основі сигналів з комп’ютера та спеціальне програмне забезпечення. Робота з тактильним дисплеєм відбувається завдяки подачі постійного струму через електромеханічні елементи. Окрему увагу приділено компоновці елементів на схемі та можливості використання комплексу у мережі. Результати дослідження можна використовувати для випуску навчальних електронних пристроїв для людей з вадами зору.

In this article the hardware and software complex for Braille font is observed. This complex consists of tactile display for six-dot symbol output and specialized software.In this work, analysis of development and implementation of systems for visually impaired reading in Braille education took place and market of exist-ing devices with common functionality was reviewed. As a result, hardware and software complex was developed, tested, and had its functional modules, operational principles of hardware and software ele-ments documented. For the first time, approach of using the enlarged Braille font in electronic educational devices for visually impaired was used (analogous systems initial-ly was built using standard six-dot size, which caused complications on the symbols memorizing stage). Practical value of conducted research is lies in detailed documentation of hardware and software complex realization. This can be a significant simplifi-cation when industrial making of educational systems for visually impaired will take place, since in article element arrangement and ability of complex’s net-work application are stressed. Research results can be used not only for production of electronic educational devices, not only for visually impaired, but also for teachers of blind students, as a medium to speed up and simplify learning of Braille font.
Realization approaches of hardware and software education complex for Braille font reading
Keywords: система Брайля; навчання інвалідів зору; програмне забезпечення; тактильний дисплей; hardware and software complex; Braille font; visually impaired education; software